An Overview of The Implementation of Pharmaceutical Service Standards at Puskesmas in Tarakan City in 2024 - Syam, Siti Muti'ah; Irma Novrianti; Jufri Ubrusun (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Pharmaceutical services that are guided by Permenkes No. 74 of 2016 in the form of presentation and accountability for patients who are directly related to pharmaceutical products at public health centers throughout Tarakan City to become a starting point for optimizing service quality and supporting the progress of the health sector that contributes comprehensively. The purpose of the study was to describe the implementation of pharmaceutical service standards in all community health centers in Tarakan City. Descriptive strategy observation research method through survey media. The results of research on 6 Puskesmas that have a pharmacist in charge can be described that the implementation of pharmaceutical service standards has been successfully implemented in all Puskesmas of Tarakan City by 83.5%, covering the first aspect of clinical pharmacy (69.1%) and the second aspect of the management of pharmaceutical preparations and consumable medical materials (97.9%). The study concluded that most of the implementation was dominated by the Pharmacist in Charge (53.6%), followed by Pharmacy Vocational Workers (24.2%) and Pharmacist Assistants (5.6%).